(untitled) - Bacal, Robert (New York, NY., 2005)
Dramatically increased productivity is the primary driver of growth in today's workplace. But productivity improvements don't occur in a vacuum--they require knowledge, action, and a commitment to performance on the part of frontline supervisors and managers. How to Manage Performance provides managers with goal-focused, commonsense techniques to stimulate employee productivity in any environment. This results-based guidebook features 24 invaluable strategies and action steps you can use to communicate the performance you expect from--and the incentives you can offer to--high-performing employees. Let this concise, dynamic book show you how to: Manage performance, Work with employees, Set performance incentives,...While performance itself may be a wide-ranging, difficult-to-quantify word, the results of improved performance are easy to measure--and can mean the difference between competitive strength and vulnerability. Discover techniques you can use to inspire breakthrough performance, and infuse both your employees and your career with renewed commitment and success, in How to Manage Performance.
Keywords: Achievement motivation.,Performance standards.,Performance; Evaluation